Factors Related to The Incidence of Stunting in The Work Area of Oekabiti Community Health Center, Kupang Regency - Finit, Karmila; Liufeto, Mega (Pergizi Pangan DPD NTT, 2025)
Background: Stunting is a condition in which a toddler has a body length or height that is lacking or not appropriate when compared to age. Data on stunting cases at the Oekabiti Health Center from year to year in succession from 2020 and 2021 are 24.8% and 20.5%. Although the incidence of stunting has decreased, it is still a health problem that must be addressed. Objectives: This study aims to determine the factors associated with the incidence of stunting in the working area of ​​the Oekabiti Health Center, Kupang Regency in 2022. Methods: This type of research is an analytical survey, with a case-control design. The sample consisted of 142 toddlers consisting of 71 case samples and 71 control samples. Case and control samples were taken using simple random sampling techniques. Data collection was carried out by interviews, observations, filling out questionnaires, and documentation. Data analysis was carried out using univariate, bivariate, and multivariate analysis. Results: The results of the multivariate analysis showed a relationship between the history of exclusive breastfeeding (p-value = 0.005), history of LBW (p-value = 0.000) and maternal knowledge (p-value = 0.001). Conclusions: The history of LBW is the most related variable and has the greatest risk of stunting. It is hoped that the community, especially women of childbearing age (WUS), will know and prepare nutrition before planning a pregnancy and be more active in going to the integrated health post to get information about nutrition and also to monitor the nutritional status of toddlers.